Accidental plant poisoning of sheep in an arid zone of Nigeria - Onyeyili, P.A.=700 1 Chibuzo, G.A.; Brisibe, F.; Egwu, G.O.
(Fr, Es)
Ilus., 11 ref.
Keywords: OVINOS; ENVENENAMIENTO; PLANTAS TOXICAS; NIGERIA; ZYGADENUS CHLORANTUS; REVISTA MUNDIAL DE ZOOTECNIA